2009
DOI: 10.1177/0022034509342523
|View full text |Cite
|
Sign up to set email alerts
|

Poisson Analysis of Streptococcal Bond-strengthening on Saliva-coated Enamel

Abstract: The forces responsible for bond-strengthening in initial oral bacterial adhesion are unknown. Since Lifshitz-Van der Waals and electrostatic forces work instantaneously upon approach, it is hypothesized that bond-strengthening is governed by hydrogen bonding. Poisson analysis of adhesion forces observed during the retraction of bacterial probes from surfaces in atomic force microscopy can be used to analyze the nature of the adhesion forces. Streptococcal adhesion forces increased from about -0.7 to -10.3 nN w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 12 publications
2
31
0
Order By: Relevance
“…Similar results have been previously observed for other streptococcal strains. 26,33 It is important to note that Ti surfaces employed in this research are clinically analogous substrates and therefore, differences in force measurements caused by surface topography were minimized by obtaining force-curves in several representative areas of the samples. Additionally, these results further demonstrate that bacteria, such as S. sanguinis, can attach directly onto Ti surfaces without the existence of a previously formed biological pellicle.…”
Section: S Sanguinis-ti Adhesive Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been previously observed for other streptococcal strains. 26,33 It is important to note that Ti surfaces employed in this research are clinically analogous substrates and therefore, differences in force measurements caused by surface topography were minimized by obtaining force-curves in several representative areas of the samples. Additionally, these results further demonstrate that bacteria, such as S. sanguinis, can attach directly onto Ti surfaces without the existence of a previously formed biological pellicle.…”
Section: S Sanguinis-ti Adhesive Interactionsmentioning
confidence: 99%
“…25 Additionally, values for short-range and long-range forces can be obtained by applying a Poisson analysis to the unbinding data observed at specific contact times. 26 Utilizing this approach, it is possible to quantify the values for both nonspecific and specific forces driving bacteria toward a surface of interest, and thus gain more insight on the underlying nature of bacteria-substrate interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1a shows an AFM force-distance curve for Staphylococcus epidermidis on glass with multiple peaks in the retraction curve. Considering each adhesion peak as an individual detachment event (2,5,8,10,26,27), each peak provides a specific adhesion force (F) according to equation 1, and the only variable for a given combination of bacterial strain and substratum is the number of short-range bonds (k). It should be noted that it is a tedious task to identify the minor peaks, since it is not clear a priori when a peak should be taken as an individual detachment event.…”
Section: Theoretical Background Of Poisson Analysis Of Adhesion Forcesmentioning
confidence: 99%
“…Note that f SR is the strength of an individual short-range bond, and not the total short-range force, which equals the number of short-range bonds (k) times the individual short-range-bond strength (f SR ) (see equation 1). The number of short-range bonds can vary widely, and Poisson analysis indicated that about 12 bonds were formed between an Escherichia coli strain and a silicon nitride AFM tip (2), while a single streptococcus attached to stainless steel through 60 short-range bonds (26), a number that decreased to 3 or even fewer when the steel surface was coated with saliva (27). This implies that only a very few ligandreceptor bonds are involved in the adhesion of streptococci to saliva-coated surfaces, making it doubtful whether the formation of ligand-receptor bonds should be considered a random event, as is required in Poisson analysis.…”
Section: Theoretical Background Of Poisson Analysis Of Adhesion Forcesmentioning
confidence: 99%
See 1 more Smart Citation